A cost-benefit comparison of build-to-order and hybrid build-to-order/build-to-stock assembly for automotive modules. (11th April 2023) - Jung, Emrae
Transition from mass production to mass customisation in automotive industry has been forcing vehicle manufacturers and their suppliers to find ways to cope with the new demanding environment through more flexible and efficient processes. Just-in-time delivery, modular design and assembly, synchronous production, build-to-order (BTO) and just-in-sequence delivery are some of the concepts that have been implemented in the automotive industry to be more efficient. Modularity has evolved as a concept enabling effective customisation by dividing products into smaller sub-assemblies and as a result, modular production is currently being applied by increasing number of vehicle and part manufacturers to manage the ever-changing orders of the industry. The objective of this study is to compare two different production strategies implemented by two different tier-1 module suppliers operating in automotive industry. One of the suppliers implements synchronous BTO assembly concept as it is widely used by tier-1 module suppliers while the other supplier prefers a hybrid approach. Both concepts were examined by evaluating operational cost of each one compared with the other and by considering benefit in terms of responsiveness offered in return.